Simian Virus 40-Host Cell Interactions. I. Temperature-Sensitive Regulation of SV40 T Antigen in 3T3 Mouse Cells Transformed by the ts(*)101 Temperature-Sensitive Early Mutant of SV40 - Robb, James A. (1973)
BALB/3T3 and Swiss/3T3 mouse cells transformed at permissive temperature (33 C) by the early temperature-sensitive mutant of simian virus 40 (SV40), ts(*)101, exhibited a temperature-dependent modulation of SV40 tumor (T) antigen as assayed by immunofluorescence. The percentage of T antigen-positive nuclei in ts(*)101 transformed cells was reduced at restrictive temperature (39 C) when compared to 33 C and to wild-type SV40 transformed cells at either 33 C or 39 C. The percentage of T antigen-positive nuclei in ts(*)101 transformed cells returned to the 33 C control level when the cells were shifted from 39 to 33 C. The ts(*)101 transformed cells could be superinfected with wild-type, but not ts(*)101, virions at 39 C as assayed by an increase in T antigen-positive nuclei.